A call for locally led postharvest innovation to urgently address global nutrition insecurity - Yumbya, Penina; Becker, Kristen; Gregerson, Katheryn; Hayashi, Heather; Jarman, Archie; Kabirigi, Michel; McGuire, Erin (Frontiers in Horticulture, 2025)
Reducing food loss and waste has recently gained significant global attention. However, prolonged underinvestment in efforts to tackle food loss and waste, particularly in horticultural crops, now demands accelerated, collaborative action. Neglecting to invest in postharvest initiatives in horticulture exacerbates global nutrition insecurity, diminishes global resilience to climate change impacts, wastes scarce resources, and sustains greenhouse gas emissions. Addressing food loss and waste involves tackling a complex array of issues throughout the food system, from upstream research and policy to downstream handling, and consumption. This complexity can make it challenging to develop effective, scalable interventions that demonstrate clear impacts in the short term. Integrating interdisciplinary perspective ensures that innovations are inclusive, scalable and context specific for sustained and measurable global impact. Locally led postharvest innovations are well suited to maximize vital opportunities for improved livelihoods, particularly for marginalized groups such as women who are heavily involved in postharvest activities globally. Establishing a global consensus on the importance of effective postharvest management is essential for improving access, affordability, and profitability in horticultural value chains. Achieving this requires innovations tailored to regional and local needs, improved postharvest systems, and capacity strengthening that simultaneously promote equity. A supportive policy framework is vital, promoting local expertise and balancing the benefits of export markets with regional consumption. We are calling for a reframing of the approach to reducing postharvest losses in horticulture crops to be an absolute necessity if we are to achieve the United Nations’ Sustainable Development Goals and outline our perspective in this article in order to promote a transition in approach.